DAMPAK PANDEMI COVID 19 TERHADAP KINERJA KEUANGAN SEKTOR PERBANKAN DI INDONESIA - Agung Anggoro Seto; Dian Septianti (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the impact of the Covid-19 pandemic on the financial performance of the banking sector in Indonesia. This type of research is comparative, the population in this study are all banking companies listed on the Indonesia Stock Exchange, totaling 45 companies, the sampling technique is by using purposive sampling with a total sample of 5 banking companies. The data source uses secondary data in the form of financial reports with data collection techniques using library research. The data analysis technique used the paired-sample t-test and Wilcoxon test. The results showed that there was no difference in the financial performance of the banking sector for the variables of capital, asset quality, and liquidity before and during the covid-19 pandemic with a significance value of 0.538, 0.444, and 0.191 respectively, while for the profitability variable there were differences in the profitability of banking in Indonesia before and during the covid-19 pandemic with a significance value of 0.019.